Dipylidiosis pada Pasien Kucing di Klinik RVet Bogor - Dita Pratama Putri; Risa Tiuria; Ridi Arif; Adi Winarto; Rizal Akbari (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
Cats are one of the many pets kept in Indonesia. Dipylidiasis is a disease that often occurs in cats caused by infection with the Cestode worm Dipylidium caninum. The case study at the Rvet Bogor clinic aimed to find out Dipylidiosis cases as well as its diagnostic and treatment techniques. Medical record data for September 2020 to September 2021 showed fluctuations in Dipylidiosis cases in 35 cat patients at the Rvet Bogor clinic. The highest infection of Dipylidium caninum in cats occurred during the rainy season from November 2020 to March 2021. The lowest disease of D. caninum in cats happened in the dry season in August 2021 and September 2021. The patient is a cat named Nuna with a lethargy condition and of soft stools and a there is a gravid proglottid on her perianal. Groups of D.caninum eggs were seen around the gravid proglottids found in the perianal area of Nuna cat patients. Drontal® anthelmintic was given to cats infected with D. caninum at the Rvet Bogor clinic.